2012
DOI: 10.1016/j.diabres.2012.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic prediction of postpartum diabetes in women with gestational diabetes mellitus

Abstract: The TCF7L2 rs7903146 and FTO rs8050136 polymorphisms, and particularly a weighted risk score of T2D risk alleles, predict diabetes after GDM. Further studies in other populations are needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…22 A GRS based on 13 variants at 11 known T2DM loci was associated with incident T2DM in a cohort of multiethnic women with previous gestational diabetes mellitus who underwent serial oral glucose tolerance tests for up to 5 years (HR = 1.11; P = 1.6 × 10 −4 ). 23 Similar findings were reported in a cohort of East Asian women using a 48-locus GRS; adding this GRS increased the C-statistic from 0.741 to 0.775 ( P = 0.02), with a continuous NRI of 0.430, indicative of moderate reclassification compared with the clinical model that included age, BMI, family history of T2DM, blood pressure and fasting levels of glucose and insulin. 24 Thus, including genetic risk in a prediction model could inform T2DM prediction even among populations already known to be at very high risk of developing this condition.…”
Section: Genetic Prediction Of T2dm Risksupporting
confidence: 79%
“…22 A GRS based on 13 variants at 11 known T2DM loci was associated with incident T2DM in a cohort of multiethnic women with previous gestational diabetes mellitus who underwent serial oral glucose tolerance tests for up to 5 years (HR = 1.11; P = 1.6 × 10 −4 ). 23 Similar findings were reported in a cohort of East Asian women using a 48-locus GRS; adding this GRS increased the C-statistic from 0.741 to 0.775 ( P = 0.02), with a continuous NRI of 0.430, indicative of moderate reclassification compared with the clinical model that included age, BMI, family history of T2DM, blood pressure and fasting levels of glucose and insulin. 24 Thus, including genetic risk in a prediction model could inform T2DM prediction even among populations already known to be at very high risk of developing this condition.…”
Section: Genetic Prediction Of T2dm Risksupporting
confidence: 79%
“…Furthermore, these polymorphisms are also linked to the development of truncal obesity, hypertension, and an increased risk of the metabolic syndrome [11, 25, 26]. Other authors likewise reported a higher risk of developing overt T2D in women carrying the A allele who had a history of gestational diabetes [27]. Collectively, the above findings suggest the importance of the FTO gene on influencing factors related to carbohydrate metabolism and this seems to be consistent among different racial/ethnic groups [5-8].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations have recently been evaluated to determine if they can be used to predict post‐partum diabetes in women with GDM. A Swedish cohort study reported that a transcription factor 7‐like 2 variant (TCF7L2 rs7903146) significantly predicts post‐partum diabetes where the median follow‐up period was 57 months . A prospective cohort study consisting of 395 Korean women with GDM who were followed annually for 45 months used a weighted genetic risk score (wGRS), consisting of 48 variants .…”
Section: Discussionmentioning
confidence: 99%
“…Higher fasting plasma glucose levels during pregnancy, after adjustments for body mass index (BMI) and age, have been shown to be predictors of the metabolic syndrome 40 months and 8.5 years after the index pregnancy. Genetic variations have also recently been evaluated to determine if they can be used to predict post‐partum diabetes in women with GDM . However, there have been no studies that have examined biochemical markers in addition to the postnatal OGTT.…”
Section: Introductionmentioning
confidence: 99%